Increased Requirement of Replacement Doses of Levothyroxine Caused by Liver Cirrhosis - Benvenga, Salvatore; Capodicasa, Giovanni; Perelli, Sarah; Ferrari, Silvia Martina; Fallahi, Poupak; Antonelli, Alessandro (Frontiers in Endocrinology, 2018)
Background: Levothyroxine (L-T4) is one of the top prescribed drugs, because hypothyroidism is a relatively common disorder. On the average, 70% of the orally ingested L-T4 is absorbed; an acid intragastric pH is required for optimal dissolution of the L-T4 tablet. A number of conditions/diseases of the digestive system and a number of drugs/supplements/beverages cause L-T4 malabsorption, resulting in failure of serum TSH to be normal. Only rarely liver cirrhosis is mentioned as causing L-T4 malabsorption. Case report: In this study, we report increased requirement of daily doses of L-thyroxine in two patients with the atrophic variant of Hashimoto’s thyroiditis and liver cirrhosis. In one patient, this increased requirement could have been contributed by the increased serum levels of the estrogen-dependent thyroxine-binding globulin (TBG), which is the major plasma carrier of thyroid hormones. In the other patient, we changed the L-T4 formulation from tablets to the oral liquid solution, maintaining the same daily dosage. After two months, her TSH levels fell in the normal range but it increased again when she returned to the tablet L-T4. Conclusion: In brief, liver cirrhosis can cause increased L-T4 requirements. In addition to impaired bile secretion, the mechanism could be increased serum TBG. A similar increased requirement of L-T4 is observed in other situations characterized by elevation of serum TBG. Because of better intestinal absorption, L-T4 oral liquid formulation is able to circumvent the increased need of L-T4 in these patients.